Implementing a Wiki for a cultural organization. - Suresh Kumar Chandrasekaran. (2009)
As organizations move towards the knowledge economy, unstructured information is also scattered and stored in various places like desktops, emails, directories, applications and other places. Organizations are finding much difficulty in capturing such information for the purpose of sharing and storing them in a central place so as to create a knowledge portal for future reference. The introduction of wiki technology, an online collaboration tool, finds a way to resolve this problem. The wiki is used to connect and collaborate between different groups across the globe within an organization through open communication, active participation, exchanging and organizing the information. This research study is all about the implementation of a collaboration tool, “C360 wiki”, in the online web portal “Culture 360” set up by ASEF. It allow artists, cultural-practioners and policy makers to collaborate on projects via a central place and interact with other cultural organizations through the exchange of views and ideas and keeping updated information and storing such information in an organized way. A comparative study was conducted on different wikis based on selective analysis to identify the mandatory and special features supported for collaboration in Literature Review. Based on the user requirement and collected information, an open source software called “C360” wiki using DotNetNuke architecture is designed and developed with mandatory functions. The mandatory functions include creating, modifying and deleting wiki pages or documents, viewing recent changes and wiki pages history, restoring previous version of the document to the current version and searching keywords in the available wiki pages that runs on DotNetNuke framework.